Effects of electronegative substitution on the optical and electronic properties of acenes and diazaacenes - Appleton, Anthony; Brombosz, Scott M.; Barlow, Stephen; Sears, John S.; Bredas, Jean-Luc; Marder, Seth R.; Bunz, Uwe H. F. (Nature Communications, 2010)
Large acenes, particularly pentacenes, are important in organic electronics applications such as thin-film transistors. Derivatives where CH units are substituted by sp2 nitrogen atoms are rare but of potential interest as charge-transport materials. In this article, we show that pyrazine units embedded in tetracenes and pentacenes allow for additional electronegative substituents to induce unexpected redshifts in the optical transitions of diazaacenes. The presence of the pyrazine group is critical for this effect. The decrease in transition energy in the halogenated diazaacenes is due to a disproportionate lack of stabilization of the HOMO on halogen substitution. The effect results from the unsymmetrical distribution of the HOMO, which shows decreased orbital coefficients on the ring bearing chlorine substituents. The more strongly electron-accepting cyano group is predicted to shift the transitions of diazaacenes even further to the red. Electronegative substitution impacts the electronic properties of diazaacenes to a much greater degree than expected.
Gesehen am 24.11.2022